Description of a Community-Based Exercise Program for Children With Cancer: A Sustainable, Safe, and Feasible Model. Issue 1 (January 2017) - Chamorro Viña, Carolina; Guilcher, Gregory M.T.; Schulte, Fiona; De Vries, Alexander; Schwanke, Jenna; Culos-Reed, Susan Nicole
Abstract : Background: Physical activity has emerged as a promising intervention to decrease the severity of cancer side effects. To date, only a few community-based exercise programs have been described in the literature. Of these, none have been designed to be sustainable and available as programs for pediatric cancer survivors on an ongoing basis. Methods: This article aims to describe a safe, feasible, and sustainable community-based exercise program for children with cancer. The program is offered to children on/off treatment and their siblings, between 3 and 18 years old. A multidisciplinary team developed this evidence-based program, and it is facilitated by trained volunteers. A parent survey was conducted to evaluate the quality of the program. Results: The PEER (Pediatric cancer patients and survivors Engaging in Exercise for Recovery) program is a safe, feasible, and sustainable community-based exercise program for children with cancer. From the parent satisfaction survey, all of the parents would strongly recommend the PEER program to other families. Conclusion: PEER provides an example of a community-based exercise program that has a strong pedagogical focus, is evidence-based, and is individualized, safe, feasible, and sustainable for children with cancer. On the basis of the benefit of exercise described in the literature, we believe this model of an evidence-based community intervention might decrease the burden of cancer side effects and promote the reintegration of children affected by cancer into physical activity programming in their community.